Situational diagnosis of the coverage territory of Family Health Strategy Maria Lúcia Gregório, in Divinópolis-MG (Research, Society and Development, 2022)
Situational diagnosis is a method of systematic analysis of the health conditions and risk of a population. In Brazil, it is used to help organize the work process of the Family Health Strategies, the primary health care program. The objective of this article is to elaborate the situational diagnosis of the ESF Maria Lúcia Gregório, in Divinópolis-MG. This is a cross-sectional descriptive study with a quantitative approach. Secondary data from the Integrated Health System were used to study the sociodemographic and health profile of the population registered with the afore mentioned Family Health Strategie. The area covered by the ESF Maria Lúcia Gregório has 1721 people registered in the SIS. 53% are women and 47% are men. 34% are affected by some health problem, especially mental health disorders and hypertension. Structural problems that affect the community and its experience were also observed. The data presented are relevant to aid in decision-making and management of health care within the ESF, in addition to being a notorious and necessary action by the government to correct the problems presented in the community.